Pendampingan Program Pendidikan Jasmani Berbasis Kearifan Lokal untuk Meningkatkan Aktivitas Fisik Anak Usia Dini di Kampung Babakan, Ciamis - Suhendra, Dede Iman; Kurniawan, Asep Ridwan; Erlina, Terra (JPKU: Jurnal Pengabdian Kesehatan Unigal, 2024)
This community service program aims to increase physical activity among early childhood children by incorporating local wisdom-based physical education. The program targeted the Learning Group (KOBAR) in Kampung Babakan, Sadewata Village, Lumbung Subdistrict, Ciamis. Methods used included presentation, demonstration, and direct practice using local traditional games. The results showed a significant improvement in children’s physical engagement and awareness of cultural heritage. The activity also encouraged community participation and helped develop a sustainable local learning model.